Spectrophotometric Evaluation of Trace level Chromium in Alloy Steel - Bhaskar, B.L.; Kumar, S. Anil; Kumar, T.M. Mohan (Asian Journal of Chemistry, 2017)
A facile and highly responsive spectrophotometric method for the quantification of ultra-trace quantities of chromium(VI) is described. The proposed method is derived from the oxidation of iminodibenzyl (IDB) with chromium in strong acid medium to get a blue coloured product, having lmax at 690 nm. Stability of the colour developed is found to be around 48 h at room temperature. Beer’s law range is observed between 0.02-0.35 μg mL-1 of chromium concentration. The coefficients of molar absorptivity and Sandell’s sensitivity are found to be 1.03 × 105 L mol-1 cm-1 and 0.000523 μg cm-2, respectively where as the detection limit is 0.9 ng mL-1. The method has been optimized for reaction conditions and optical parameters. Tolerance limits for various interfering ions were studied. The efficiency of the method was shown by successful determination of traces of chromium in alloy steel samples.